1994
DOI: 10.1111/j.1476-5381.1994.tb17020.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by SR140333 of NK1 tachykinin receptor‐evoked, nitric oxide‐dependent vasodilatation in the hamster cheek pouch microvasculature in vivo

Abstract: 1 This study investigated tachykinin-evoked vasodilatation in the microvasculature of the hamster cheek pouch in vivo. Arterioles and venules were observed by intravital microscopy with video recording, and vasodilatation and constriction, defined as changes in blood vessel diameter, measured by image analysis. All agents were applied topically by superfusion. None of the agents tested had a significant effect on venule diameter. 2 When arterioles were preconstricted (by ca. 50%) with endothelin-1 present in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…, 1998) infiltration of granulocytes (Smith et al. , 1993) and nitric oxide‐dependent vasodilatation (Hall and Brain, 1994). These effects are mediated by the NK 1 receptor and could thus be controlled by ECE‐1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 1998) infiltration of granulocytes (Smith et al. , 1993) and nitric oxide‐dependent vasodilatation (Hall and Brain, 1994). These effects are mediated by the NK 1 receptor and could thus be controlled by ECE‐1.…”
Section: Discussionmentioning
confidence: 99%
“…Whether ECE-1 regulates other effects of SP on endothelial cells remains to be determined. In addition to promoting plasma extravasation, SP acts on endothelial cells to cause expression of adhesion molecules (Quinlan et al, 1998) infiltration of granulocytes (Smith et al, 1993) and nitric oxidedependent vasodilatation (Hall and Brain, 1994). These effects are mediated by the NK1 receptor and could thus be controlled by ECE-1.…”
Section: Figurementioning
confidence: 99%
“…The time‐course of the arteriolar dilatation was similar for all agonists tested with dilatation reaching a maximum at 3–4 min and reversing after 10–20 min. The rate of onset and offset of responses of the two peptides is relatively slow when compared to certain other vasodilators such as substance P ( Hall & Brain, 1994 ), though similar to the structurally similar peptide adrenomedullin 13–52 ( Hall et al ., 1995 ). CGRP is well known to produce long‐lasting microvascular vasodilatation, characterized by a pronounced and well maintained erythema in human skin and a maintained increase in blood flow in rabbit skin ( Brain et al ., 1985 ), and prolonged decreases in perfusion pressure in isolated preparations such as the rat mesentery ( Claing et al ., 1992 ) and rat kidney ( Chin et al ., 1994 ).…”
Section: Discussionmentioning
confidence: 99%
“…Male golden (Syrian) hamsters (80–120 g) were anaesthetized with sodium pentobarbitone (Sagatal 60 mg kg −1 , i.p) and anaesthesia was maintained with 15 mg kg −1 pentobarbitone as required. A single layer of vascular membrane was prepared as described by Duling (1973) with some modifications ( Hall & Brain, 1994 ). Briefly, the hamster was placed on a specially designed stage with a central depressed well, the right cheek was carefully everted and placed in the well and pinned on a silicon‐rubber ring encircling the window.…”
Section: Methodsmentioning
confidence: 99%
“…We examined reactivity of cheek pouch arterioles in response to histamine and substance P, which release endothelium-derived relaxing factor, i.e.. nitric oxide or a nitric oxide-containing compound, in a variety of vascu lar preparations [13], We also examined responses of cheek pouch arterioles to nitroglycerin, which produces vasodilatation independent of nitric oxide synthase [13], Previous studies have shown that arterioles of the hamster cheek pouch respond to, and release nitric oxide or a ni tric oxide-containing compound, during application of mediators such as bradykinin, methacholine [14,15] and substance P [16]. Findings of the present study are in agreement with these previous studies.…”
Section: Consideration O F Methodsmentioning
confidence: 99%